Prodromal symptoms as unfamiliar feelings: Experiences of Iranian myocardial infarction patients - Lida Soltani; Ali Ravari; Tayebeh Mirzaie; Behnaz Bagherian; Sakineh Sabzevari (ARYA Atherosclerosis, 2021)
BACKGROUND: Patients affected by myocardial infarction (MI) report prodromal symptoms before heart attack. Deep understanding of these symptoms can increase the likelihood of early recognition and treatment of coronary heart disease (CHD). The purpose of this study was to describe the prodromal symptoms of MI experienced by Iranian adults.METHODS: In this qualitative conventional content analysis, data was collected through an in-depth semi-structured interview with 14 men and women (aged 40–82 years). The patients were interviewed at the hospital 2 or 3 days after hospitalization due to MI. MAXQDA software was used for data analysis.RESULTS: Data analysis led to the emergence of the 4 categories of ‘Misperception of the symptoms’, ‘Reactions to the symptoms’, ‘Heart disease knowledge deficit’, and ‘Ideas and beliefs about heart disease’. The participants had not recognized the prodromal symptoms of MI and they attributed their symptoms to non-cardiac causes. They did not consider themselves at risk of heart disease, so they did not seek health services.CONCLUSION: The participants were unaware of their prodromal symptoms. Clinicians should be attentive that men and women at risk of MI may experience a range of unfamiliar and vague prodromal symptoms, so they must give greater attention to their narratives. A greater understanding of the prodromal symptoms experienced may lead to a more truthful and timely interpretation of their symptoms and earlier detection by physicians.